Enzyme-Free Electrochemical Nano-Immunosensor Based on Graphene Quantum Dots and Gold Nanoparticles for Cardiac Biomarker Determination - Bhargav D. Mansuriya; Zeynep Altintas (Nanomaterials, 2021)
An ultrasensitive enzyme-free electrochemical nano-immunosensor based on a screen-printed gold electrode (SPGE) modified with graphene quantum dots (GQDs) and gold nanoparticles (AuNPs) was engineered to detect cardiac troponin-I (cTnI) for the early diagnosis of acute myocardial infarction (AMI). The GQDs and in-house synthesized AuNPs were implanted onto the SPGE and allowed for anti-cTnI immobilization prior to quantifying cTnI. The biomarker could be determined in a wide concentration range using square-wave voltammetry (SWV), cyclic voltammetry (CV), electron impedance spectroscopy (EIS) and amperometry. The analyses were performed in buffer, as well as in human serum, in the investigation ranges of 1–1000 and 10–1000 pg mL−1, respectively. The detection time ranged from 10.5–13 min, depending on the electrochemical method employed. The detection limit was calculated as 0.1 and 0.5 pg mL−1 for buffer and serum, respectively. The sensitivity of the immunosensor was found to be 6.81 µA cm−2 pg mL−1, whereas the binding affinity was determined to be <0.89 pM. The sensor showed high specificity for cTnI with slight responses for nonspecific biomolecules. Each step of the sensor fabrication was characterized using CV, SWV, EIS and atomic force microscopy (AFM). Moreover, AuNPs, GQDs and their nanocomposites were characterized by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). This is the first immunosensor that represents the successful determination of an analyte using four different electrochemical techniques. Such a sensor could demonstrate a promising future for on-site detection of AMI with its sensitivity, cost-effectiveness, rapidity and specificity.